The poems of MS Junius 11 : basic readings - Liuzza, R. M. (Basic readings in Anglo-Saxon England., 2002)
"Found in a manuscript of Anglo-Saxon verse known as Junius 11, the biblical poems Genesis, Exodus, Daniel, and Christ and Satan have fascinated scholars for centuries. The manuscript, published by its owner Franciscus Junius in 1655, was the first codex of Old English poetry to appear in print. Written sometime around 1000, these works were originally attributed by Junius to the poet Caedmon, but they are now generally believed to be the work of several authors. However, the selection and arrangement of the texts continue to pose questions about their meaning, source, authorship, and audience that challenge our efforts to understand the manuscript as a whole and the individual poems themselves." "In this volume, R.M. Liuzza has brought together a collection of essays that analyze the Junius poems from a variety of theological, rhetorical, cultural, textual, and literary perspectives. The contributors illuminate the Junius poems as treasuries of Anglo-Saxon religious lore, rich fusions of sources and influences, and complex sites of the acculturation of Christianity in the Germanic world. Together, the essays illuminate the challenges of these intriguing poems and enrich our understanding of their literary significance, their unique material context, and the hybrid culture that produced them."--Jacket